Geographical Distribution of Death due to Cancer in Kerman Province, Southeast Iran - Parvin Khalili; Mohsen Rezaeian; Abdolhalim Rajabi; Ali Gholami; Mahin Saber; Ahmad Jamalizadeh; Mina Hosseini; Reza Vazirinejad (علوم بهداشتی ایران, 2019)
Background: In Iran, cancer kills 30,000 people, annually. The epidemiology of cancer is gradually changing as a result of the demographic and epidemiological transition in Iran. This study aimed at presenting a geographical distribution of cancer mortality in Southeast area of Iran, and comparing proportional mortality and age-adjusted mortality rates. Methods: The present study was a descriptive study that was performed on mortality data recorded in the Center for Statistics Management of Health Ministry at Kerman and Rafsanjan Universities of Medical Sciences in the period 2012-2016. This information was used to determine the age-standardized mortality rate per 100,000 people and proportional mortality for each district in Kerman Province. Results: The proportional mortality for all cancers in Kerman and Rafsanjan Universities were 11.54% and 18%, respectively. Standardized mortality rates for all cancers in males in Kerman and Rafsanjan universities were also 81.9 and 81.3 per 100,000, respectively, while for females, it was 57.3 and 51.6 per 100,000 people, respectively. Conclusion: Our results presented a general picture of the mortality due to cancer in one of the widest provinces of the country with more than 1.5 million habitants .Standardized mortality rates for all cancers in males and females in Rafsanjan universities was lower than Kerman. In spite of higher proportional mortality in Rafsanjan, the rate of death by cancer in Rafsanjan was lower than Kerman.